21st century engineering for on-farm food–energy–water systems. (November 2017) - Wolfe, Mary Leigh; Richard, Tom L
Highlights: Reduce inputs while improving crop yield and quality to increase profitability. Integrate biomass crops with food crops to increase productivity of the landscape. Agriculturally oriented IT companies help farmers evaluate data-intensive options. Additional value of ecosystem services can provide incentives for change. Abstract : For more than a century, agricultural mechanization encouraged larger fields with more uniform management and increasing impacts on the environment. The trajectory of agricultural technology is now at an inflection point where information technology, including remote sensing, simulation modeling, decision support systems, precision agricultural technologies, and automation, enables site-specific management at small spatial scales with the potential to simultaneously enhance food and bioenergy production, farm profitability, and environmental quality. To achieve these economic and environmental benefits of transforming agricultural landscape design and cropping system management, agricultural producers need increased access to both enabling technologies and engineering expertise. Government policies and programs are also needed to incentivize changes in cropping systems that promote soil health and improve water quality, for example, payments to cover much or all of the cost of transitioning land use to perennials and nutrient trading programs in which agricultural producers contract with industrial and municipal wastewater generators to reduce nutrient loading at a reduced cost. Information technology is providing the tools to target, quantify, and document this re-coupling of economic, environmental, and social sustainability in food–energy–water systems.